The friars in the Philippines - Coleman, Ambrose (Marlier, Callanan, 1899)
"The following pages originally appeared as magazine articles. In both England and America the papers were favorably received; and as the public has not heard the last of the Friars in the Philippines, it seemed worth while to reproduce them in the more permanent form of a small volume, making such corrections and additions as might be deemed advisable. Whatever may be the shortcomings of the book, there is a real and pressing need for the information it contains, and this need must remain the excuse for its imperfections."